One‐Pot Synthesis of Functionalized Isoindolinones and Their Bis(isoindolinone)ethane Derivatives. Issue 47 (15th December 2022) - Purohit, Deepak; Singh Rawat, Kundan; Parveen, Sajiya; Prakash Vats, Ravi; Prakash Sharma, Chandra; Goel, Atul
Abstract: Highly efficient one‐pot synthesis of a series of substituted 3‐methylene‐isoindolinones (3 a –x ), bis(isoindolinone)ethanes (4 a –d ) and 3‐hydroxy‐isoindolinones (6 a –h ) derivatives is portrayed from easily accessible starting materials such as 2‐cyanobenzaldehydes (1 a –h ) and different aryl/heteroaryl methyl ketones (2 a –k ). The structure of Z‐isomer of 3‐methylene‐isoindolinone 3 x was confirmed by single crystal X‐ray analysis. The reaction mechanism studies by control experiments and using O 18 ‐labelled water revealed that the reaction was initiated by attack of a conjugate base of aryl/heteroaryl methyl ketones (2 a –k ) to aldehyde group of 1 a –h followed by intramolecular oxidative cyclization involving nitrile functionality to furnish isoindolinone derivatives in good to excellent yields. Abstract : A one‐pot synthesis of a series of substituted 3‐methylene‐isoindolinones (3 a –x ), bis(isoindolinone)ethanes (4 a –d ) and 3‐hydroxy‐isoindolinones (6 a –h ) derivatives is described.